Hubungan antara Tingkat Pendidikan dan Jarak Kehamilan dengan Kadar Hemoglobin pada Ibu Hamil: Sebuah Tinjauan Literatur - Muhammad Fauzan Iqbal; Sutarto; Anisa Nuraisa Jausal; Rodiani (Jurnal Riset Multidisiplin Edukasi, 2025)
Decreased hemoglobin (Hb) levels during pregnancy are a public health problem that is still widely found, especially in low- and middle-income countries, and contributes to increased maternal and perinatal morbidity and mortality. Pregnant women are a vulnerable group due to increased iron requirements and physiological changes during pregnancy. This study aims to systematically review the relationship between education level and interpregnancy interval with hemoglobin levels in pregnant women. The method used was a structured narrative literature review with literature searches on the PubMed, ScienceDirect, Google Scholar, and Garuda databases. The articles included were quantitative studies on pregnant women published in the last five years (2021–2025) and reporting the relationship between education level or interpregnancy interval and anemia or hemoglobin levels. The synthesis results showed that education level indirectly affects hemoglobin levels through health literacy, nutritional knowledge, adherence to iron supplementation, and utilization of antenatal services. Mothers with low education tend to have lower hemoglobin levels due to limited understanding and preventive behaviors against anemia, although this effect may be weakened in contexts with good access to information and health services. Short interpregnancy intervals (less than 24 months) are consistently associated with decreased hemoglobin levels through the mechanisms of incomplete recovery of iron reserves after childbirth and increased physiological stress. Overall, education and interpregnancy interval affect hemoglobin levels through interrelated cognitive, behavioral, and biological pathways, necessitating an integrated intervention approach for anemia prevention in pregnant women.